Design of an impact absorbing green composite. (2022) - Oztemur, Janset; Sezgin, Hande; Yalcin-Enis, Ipek
Abstract: The goal of this study is to build impact-absorbing bio-composite panels from bio-resin and denim wastes that can help solid waste management. Within this scope, composite structures with different layer numbers are produced using waste denim fabric and epoxy:AESO (70:30) matrix material. The panels produced in different number of layers are subjected to physical (density and fiber weight ratio) and mechanical (drop-weight resistance) tests. The drop impact resistance test results show the increasing number of layers in the composite structure improves the impact resistance.